Hubungan Tingkat Pengetahuan, Sikap Dan Perilaku Pencegahan Tuberkulosis Di Distrik Meyado, Kabupaten Teluk Bintuni, Papua Barat - Febriani Robeka Wanma; Kukuh Pambuka Putra; Arwyn Weynand Nusawakan (Jurnal Keperawatan Muhammadiyah, 2020)
World Health Organization states that in 2017 Tuberculosis cases are estimated to reach 842 thousand cases and 116 thousand deaths. Indonesia ranks third after India with 2.4 million cases and China with 889 thousand cases from all sufferers in the world. BTA + cases in Teluk Bintuni Regency in 2017 were 192 cases, 2018 were 265 cases and 2019 were 264 cases. The purpose of this study is to describe the level of knowledge, attitudes and behaviors in preventing Tuberculosis. Method: The type of research used is Observational Analytic. Research site in Meyado District, Bintuni Regency, West Papua. Samples 88 respondents, The sampling technique uses simple random sampling. The research instrument used a questionnaire. Results: respondents with a level of knowledge of less than 42 people (48%), 32 people enough (36%) and good 14 people (16%). Respondents with negative attitudes 65 people (74%) while positive attitudes 23 people (26%). The respondent's behavior is quite 49 people (56%), less behavior 25 people (28%) and good behavior is 14 people (16%). The Spearman rho test showed no relationship between the level of knowledge with tuberculosis prevention behavior (p value = 0.214), and there was a relationship between attitudes and tuberculosis prevention behavior (p value = 0,000).